Analisis Keuangan Keluarga di Masa Pandemi Covid 19 - Yuli Siyamto; Asron Saputra (LPPM Universitas Putera Batam, 2020)
The Covid 19 pandemic has spread throughout the world, including Indonesia. The effects of the pandemic caused the national economy to decline by minus 5.23%. In Batam City, the Covid 19 Pandemic caused many small, medium and large businesses to go out of business. The direct effect of the pandemic on the lower middle class is the financial turmoil of the family. There was a decrease in income and expenditure as well as a change in the clustering of expenditure items. Internet quota has become a mandatory expense for education. The initial objective of this study was to obtain facts, the current condition of society. The research object is the middle to lower class of society. This research is a descriptive qualitative research. Collecting data in research using the method of observation and questionnaires. Observation through limited interviews, by observing and visiting and discussing directly with the community. People also fill out an online questionnaire via a google form link, to reduce physical contact. The sample size was determined by accidential sampling method. The results showed that 80% of respondents experienced a decrease in the number of stages during the COVID 19 pandemic. Meanwhile, respondents have a job from home (WFH), have courageous schooling, are in the trend of family spending on food, electricity bills, water bills, and education quota costs. The final objective of this research is expected to be additional material for the Batam City government in economic policies that can help the life and welfare of the community.